Nuansa Tafsir Bi al-Riwayah dalam Al-Qur’an dan Tafsirnya Departemen Agama RI yang Disempurnakan: Telaah terhadap Ayat-Ayat Perdagangan dan Larangan Riba - Hidayati, Hidayati (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
The method of interpreting of Koran using the transmitted interpretation (tafsir bi al-riwayah) is still relevant to be applied in this era, although it is less developed, compared with logical interpretation of Koran (tafsir bi al-ra’yi). This idea has showed up in reality through the findings of transmission based interpretation in many Indonesian interpretation of Koran (tafsir) books, which are classified as logic based interpretation, (tafsir bi al-ra’yi), such as Tafsir of Koran Published by Religious Affairs Department of RI. This book of interpretation of Koran combine the two methods of interpretation of Koran, the transmission basis, and the logical basis (tafsir bi al-riwayah, and tafsir bi al-ra'yi) in the interpretation of Koran, especially in modern issues. There are two data resources in this research, which are primary and secondary. The primary resourses is The Koran, and Tafsir of Koran Published by Religious Affairs Department of RI. Meanwhile, the secondary resources are books and information taken from scientific works and articles such as thesis, dissertation, journals, and other literatures. The approaches that are used in this research is interpretation of Koran approach. The data collected was analysed with descriptive approach.